Mesoscopic model applied to DNA/TNA hybrids and DNA in solutions containing Mg2+ - Maria Izabel Muniz Foscarini (2022)
When the double-stranded helix of nucleic acids is influenced by conditions such as increase the temperature of the solution, change pH and chemical agent (formamide, ethylene glycol and urea for example), this stable structure may unwind, due to the disruption of hydrogen bonds between base pairs, leading to two separate single strands. This phenomenon is called denaturation, and can be described by physical statistical and mesoscopic model called Peyrard-Bishop (PB) model. The PB model considers two interaction potentials: Morse and harmonic potential. The Morse potential as the connecting hydrogen bonds in two bases on opposite strands forming base pairs, and the harmonic potential as the stacking interaction between two neighboring base pairs. One of the advantages of the model is that it can be used to determine the strength of the hydrogen bonds and stacking interactions using melting temperatures as experimental input. Here, we use this approach for two projects, in one we study a modified nucleic acid and in the other we investigate the effects of divalent cations in DNA melting. In the first project, we used measured melting temperatures to obtain an estimate of hydrogen bonds and stacking interactions of a modified nucleic acid called threose nucleic acid (TNA) (alpha-L-(3'-2')-threofuranosyl nucleic acid) which has a backbone that is one atom shorter than DNA and RNA, but can still form anti-parallel duplexes. TNA is of practical interest as it is resistant to nuclease degradation and therefore of interest for biotechnological applications. Our results indicated that TNA/DNA hybrids share several similarities with RNA/DNA, such as the tendency to form A-type helices and a strong dependency of their thermodynamic properties on purine/pyrimidine ratio. Furthermore, for AT base pairs in DNA/TNA have nearly identical hydrogen bond strengths than their counterparts in RNA/DNA, but surprisingly CG turned out to be much weaker despite similar stability. On the other hand, the stacking interactions were found to be stronger for DNA/TNA than for DNA/RNA. In the second project, we evaluate sequences of DNA melting temperatures in Mg2+ and Mg2+ + K+ buffers with a mesoscopic model, making a distinction between internal and terminal base pairs. In addition to this distinction of the base pair position, we investigate via PB model multiple concentrations of Mg2+ to understand how they affect DNA stability. This study is of interest for PCR diagnostics which rely on enzymatic reactions performed that require Mg2+. The Mg2+ and Mg2+ + K+ results are compared to previous calculations for Na+, in terms of equivalent sodium concentration and ionic strength, and we show that the resulting hydrogen bond potentials can be related by the equivalent sodium concentration of Mg2+, so the Morse potentials are essentially constant and unaffected by cation conditions. Considering the sodium equivalence, we found that the resulting hydrogen bond do not change, regardless of ion valence and concentration. For stacking interactions on the other hand we find a clear dependence of ionic strength and cation valence. The highest ionic strength variations, for both hydrogen bonds and stacking interactions, was found at the sequence termini. In these projects using the PB model, we were able to understand the thermal stability of a xeno nucleic acid and the influence of a divalent ion on DNA. Our results have deepened our understanding of TNA and answered several questions regarding the influence of Mg2+ in DNA.